Recurrence and Progression of Head and Neck Paragangliomas after Treatment. (April 2020) - Contrera, Kevin J.; Yong, Valeda; Reddy, Chandana A.; Liu, Sara W.; Lorenz, Robert R.
Objective: To characterize the recurrence of head and neck paragangliomas and the factors associated with disease progression after treatment. Study Design: Retrospective cohort study. Setting: Tertiary care center. Subjects and Methods: In total, 173 adults with 189 paragangliomas (41.3% carotid body, 29.1% glomus jugulare, 19.0% glomus tympanicum, and 10.6% glomus vagale) treated between 1990 and 2010 were evaluated to determine the incidence and risk of recurrence using Cox proportional hazards. Results: The mean (SD) follow-up duration was 8.6 (9.1) years. The incidence was 2.92 recurrences per 100 person-years. The rate of recurrence was 8.2% (95% confidence interval [CI], 3.7-12.7) after 4 years and 17.1% (95% CI, 10.2-24.0) after 10 years. Glomus jugulare tumors were more likely to recur (hazard ratio [HR], 3.69; 95% CI, 1.70-8.01; P < .001) while carotid body tumors were less likely (HR, 0.44; 95% CI, 0.21-0.97; P = .041). Radiation had a lower risk of recurrence or progression compared to surgical excision (HR, 0.30; 95% CI, 0.10-.94; P = .040). Recurrence was associated with right-sided paragangliomas (HR, 3.60; 95% CI, 1.63-7.75; P = .001). The median time to recurrence was 18.4 years. Six (3.2%) patients developed metastasis, which was more common with local recurrence (9.5% vs 1.4%, P = .015). Conclusions: Recurrence is more common with glomus jugulare tumors and less common with carotid body tumors. Radiation may have a lower risk of recurrence or progression than surgery for some paraganglioma types. Metastasis is rare but more likely with recurrent disease. Surveillance neck imaging is recommended every several years for decades after treatment.